The association between frailty and falls among individuals aged 60 years and older residing in community settings and experiencing hip fractures in China: a cross-sectional study - Lan Jiang; Shulong Ding; Juxia Wang (The Aging Male)
Objectives Previous studies have established a correlation between frailty and an increased risk of falls among middle-aged and elderly individuals within community settings. The frailty status of hospitalized and community-dwelling adults aged 60 or older with hip fractures is poorly investigated. This study aims to examine the relationship between frailty status and falls in China among community-dwelling and hospitalized individuals with hip fractures aged 60 and older.Methods Data from the Huangshan City People’s Hospital’s Department of Trauma and Orthopedics (a single center), and the China Health and Retirement Longitudinal Study (CHARLS) were used in this investigation. Falls were self-reported, and frailty was measured using the FRAIL scale. The association between frailty and falls was examined using logistic regression models, restricted cubic splines (RCS), and subgroup analysis. Appropriate adjustments were made for confounding factors, such as age, gender, marital status, education level, smoking, drinking, body mass index (BMI), hearing and vision impairment, hypertension, diabetes, medication history, exercise, and hip fracture.Results After applying the inclusion and exclusion criteria, 5224 subjects from CHARLS (male: 52.2%, female: 47.8%) and 174 patients from the trauma and orthopedic ward (male: 36.2%, female: 63.8%) were included. Analysis revealed a strong association between each additional point in the frailty score and an increased risk of fall in patients aged 60 and older (CHARLS, OR: 1.53, 95% CI: 1.41–1.66; A single center, OR: 1.57, 95% CI: 0.92–2.71). This association was even more pronounced in the pre-frail (CHARLS, OR: 1.95, 95% CI: 1.65–2.32; A single center, OR: 1.67, 95% CI: 0.46–6.08) and frail (CHARLS, OR: 3.43, 95% CI: 2.51–4.68; A single center, OR: 4.01, 95% CI: 0.61–26.41) groups compared to the control group. Subgroup studies revealed a sex-related interaction between frailty and falls in patients with hip fractures but not in older persons residing in the community. Furthermore, RCS regression revealed a linear correlation between frailty and falls in both groups.Conclusions This study found a positive association between frailty status and falls in CHARLS and hip fracture patients from a single center. Gender differences in this relationship were observed only in hip fracture patients. These findings highlight the importance of frailty to community workers and clinical practitioners.